Recent observation of anomalous superconducting behavior of ultrathin YBCO films and single crystals of cluster borides - Gasparov, V.A. (Физика низких температур, 2006)
We report the number of deviations from conventional behavior in superconducting properties of ultrathin (1–3 unit-cell (UC)) YBa₀₂Cu₃O₇₋x films sandwiched between semiconducting Pr₀,₆Y₀,₄Ba₂Cu₃O₇₋x layers and for single crystals of cluster superconductor: dodecaboride ZrB₁₂. We have found a quadratic temperature dependence of the kinetic inductance, Lk⁻¹(Т) , at low temperatures independent of frequency, with a break in slope at TBKT dc , the maximum of real part of conductance, ωσ₁(T), and a large shift of the break temperature and the maximum position to higher temperatures with increasing frequency ω. We obtain from these data the universal ratio T /Lk⁻¹ (Tdc ) = 25, 25, and 17 nHK for 1-, 2- and 3-UC films, respectively in close agreement with theoretical prediction for vortex—antivortex unbinding transition. Superfluid density of ZrB₁₂ displays unconventional temperature dependence with pronounced shoulder at T/Tc equal to 0.65. Contrary to conventional theories we found a linear temperature dependence of Hс₂(Т) from Tc down to 0.35 K. We suggest that both λ(T) and Hс₂(Т) dependencies can be explained by a two band BCS model with different superconducting gap and Tc.